Credit supply dynamics and economic activity in euro area countries: a time-varying parameter VAR analysis - Martin Bijsterbosch; Matteo Falagiarda (European Central Bank (ECB), 2014)
This paper aims to shed light on the role of credit supply shocks in euro area countries during the recent pre-crisis, bust, and post-crisis periods. A time-varying parameter vector autoregression (TVP-VAR) with stochastic volatility à la Primiceri (2005) is estimated for each country, and the structural shocks are identified by imposing sign restrictions on impulse response functions based on the theoretical model by Gerali et al. (2010). The results suggest that credit supply shocks have been an important driver of business cycle fluctuations in euro area countries, and that their effects on the economy have generally increased since the recent crisis. Moreover, we report evidence that credit supply shocks contributed positively to output growth during the pre-crisis period and negatively during the downturn in economic activity in 2008-2009 in all the countries considered. In the post-crisis period, by contrast, we observe a strong rise in cross-country heterogeneity, reflecting financial fragmentation in the euro area. Although this heterogeneity across euro area countries seems to have declined since around 2012, the contribution of credit supply shocks to GDP growth and credit growth remains negative in most euro area countries, suggesting that constraints in the supply of credit continue to weaken economic activity.
Keywords: C11; C32; E32; E51; 330; credit supply shocks; euro area; sign restrictions; TVP-VAR